Test the Effectiveness of Reed Diffuser Fragrant Pandan Leaf Extract as a Vector Repellent of House Flies (Musca domestica) - Delavita Yunus; Herlina Jusuf; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Flies play a big role in public health problems because they serve as vectors for disease transmission. Diseases transmitted by flies include typhus abdominalis, salmonellosis, cholera, and dysentery. The use of natural insecticides is a safe control alternative, one of which is by utilizing plants that are easy to grow, obtain, process, and beneficial for health such as fragrant pandan leaves. The purpose of the study was to test the effectiveness of the fragrant pandan leaf extract reed diffuser as a vector repellent of the house fly (Musca domestica). This type of research is experimental with a Quasi Experimental design using a Group Random Design (RAK). The study sample was 120 adult house flies randomly taken from the environment and used for 3 repetitions. Data were analyzed using the One Way Anova test with an error rate (?) = 0.05 The results showed that the average mortality of house flies killed at concentrations of 15%, 20%, and 25% with a fragrant pandan leaf extract diffuser was 5 (50%), 7 (70%), and 9 (90%) respectively. There is a significant difference with (p-value = 0.003). It is recommended for future researchers to use time variations to look at the mortality of house flies (Musca domestica).